NATO, EU Lose Some Luster in the Eyes of Bulgarian Public, But Many Still Want To Join. - United States Information Agency. Office of Research and Media Reaction.; Fleury, Christopher J. (Tufts University. Tisch Library., 2019)
Probably reflecting uneasiness over Kosovo, Bulgarian public attitudes toward the international community have worsened modestly since last year. Nonetheless, this USIA poll in Bulgaria shows that recent events have not dampened public sentiment for joining western organizations such as NATO and the EU.; Opinion Analysis M-107-99